Domestic Violence Through Digital Platforms - Muhammad Hidayat; Bashori Alwi (Anjasmoro: Islamic Interdisciplinary Journal, 2026)
This study aims to analyze the role of social media in the dissemination of information related to domestic violence (DV) in the digital era and its law enforcement mechanisms. Domestic violence is a human rights violation that includes physical, psychological, sexual, and economic violence, with the majority of victims being women and children. This study uses qualitative methods with a virtual ethnography (netnography) approach to examine community interactions and responses on social media. The results show that social media plays a role as a reporting tool, a space for public participation, and an educational medium that raises public awareness and helps victims gain public support that encourages a response from law enforcement. However, its use remains restricted by the Electronic Information and Transactions (ITE) Law to prevent violations of the law. Law enforcement is carried out through the synergy of the Domestic Violence Law, the Electronic Information and Transactions Law, and the TPKS Law, although its effectiveness is still influenced by the community's digital literacy.